Penerapan Latihan Hand Paddel terhadap Kecepatan Renang Gaya Bebas Atlet Pemula Noren Tirta Buana Swimming Club - Yuliana, Sevi; Darsi, Helvi; Remora, Hengky (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
This study aims to determine whether there is an increase after the application of Hand paddel training to swimming speed of 50 meters freestyle in beginner athletes. The research method used in this research is the pre-experimental method with the research design using one group pretest-posttest design. This research was conducted at Noren Tirta Buana Swimming Club with a sample of 20 young athletes in the age group III and IV selected using total sampling technique. The results of the study concluded that there was an increase after the application of the exercise using Hand paddels to the 50 meter freestyle swimming speed of the novice athlete Noren Tirta Buana Swimming Club, this is evidenced from the results of statistical analysis that the t-count value (t-count > t-table) (1,51 > 0.13), the increase in pretest and posttest was 2,93%, so the hypothesis that Hand paddels can increase the speed of 50 meters freestyle can be accepted.